Utilization of Papaya and Tomatoes in Making Jelly Drinks Source of Vitamin C - Ariyani, Putri Sukmawati; Iswahyudi; Siregar, Maruli (Jurnal Kesehatan, 2024)
Introduction: Papaya and tomatoes are local food ingredients that are easily found in the community and contain vitamin C to be developed into functional foods, one of which is as a jelly drink. This research aims to use papaya and tomatoes as raw materials for making jelly drinks as a source of vitamin C. Method: This research used a Completely Randomized Design (CRD) with two repetitions. The factors in the study are the comparison of papaya and tomato juice, which consists of 3 levels, namely F1 (60%: 40%), F2 (70%: 30%), F3 (80%: 20%), and F0 (0%:0%) as control. The organoleptic test uses hedonic and hedonic quality tests with 50 untrained panelists. The chemical analysis carried out includes water content, ash content, protein, fat, carbohydrates, and vitamin C in the entire formula. Data analysis was carried out using the ANOVA test and Kruskal Wallis test, followed by the Duncan and Mann-Whitney tests at a significance level of 95%. Result: The results of the organoleptic test showed that each formulation treatment had a significant effect on the level of preference and hedonic quality of color, aroma, texture, and taste (p<0.05). The results of the chemical analysis show that papaya and tomatoes in making jelly drinks have a significant effect on the levels of water, ash, protein, fat, carbohydrates, and vitamin C. Conclusion: Jelly drink was selected based on the results of hedonic test analysis and hedonic quality using weighting based on the Exponential Comparison Method (MPE), namely F2 (papaya 360 g and tomato 240 g) with nutritional content per serving size of 170 mL having energy of 60 kcal, protein 0.12 g, fat 0.002 g, carbohydrates 14 g, and vitamin C 12 mg.   Pendahuluan: Pepaya dan tomat merupakan bahan pangan lokal yang mudah ditemui di masyarakat dan memiliki kandungan vitamin C untuk dikembangkan menjadi pangan fungsional salah satunya sebagai minuman jeli. Tujuan penelitian ini adalah untuk memanfaatkan buah pepaya dan tomat sebagai bahan baku pembuatan jelly drink sumber vitamin C. Metode: Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan dua kali pengulangan. Faktor dalam penelitian yaitu perbandingan sari pepaya dan tomat yang terdiri atas 3 taraf, yaitu F1 (60% : 40%), F2 (70% : 30%), F3 (80% : 20%), dan F0 (0% : 0%) sebagai kontrol. Uji organoleptik menggunakan uji hedonik dan mutu hedonik dengan 50 panelis tidak terlatih. Analisis kimia yang dilakukan meliputi kadar air, kadar abu, protein, lemak, karbohidrat, dan vitamin C pada keseluruhan formula. Analisis data dilakukan menggunakan uji ANOVA dan uji Kruskal Wallis dilanjutkan dengan uji Duncan dan Mann-Whitney pada taraf signifikansi sebesar 95%. Hasil: Hasil uji organoleptik menunjukkan bahwa tiap perlakuan formulasi berpengaruh nyata terhadap tingkat kesukaan serta mutu hedonik warna, aroma, tekstur, dan rasa (p<0,05). Hasil analisis kimia menunjukkan bahwa penambahan pepaya dan tomat dalam pembuatan jelly drink berpengaruh nyata terhadap kadar air, abu, protein, lemak, karbohidrat, dan vitamin C. Simpulan: Jelly drink terpillih yaitu F2 dengan kandungan gizi per takaran saji 170 mL memiliki energi sebesar 60 kkal, karbohidrat 14 g, dan vitamin C 12 mg.